Optical coherence tomography angiography artifactual choroidal neovascularization in optic disc pit maculopathy - Roizenblatt,Marina (2017)
ABSTRACT This case report describes a 19-year-old Caucasian man presented with decreased visual acuity in the right eye for 3 months. Dilated funds exam revealed optic disk pit associated with serous macular detachment. Optical coherence tomography identified communication between the optic disk pit and the macular serous detachment, and optical coherence tomography angiography displayed a subfoveal area suggestive of subfoveal choroidal neovascularization. However, there was no evidence of leakage in the fluorescein angiogram and no evidence of choroidal neovascularization in optical coherence tomography in the area corresponding to the suspicious subfoveal choroidal neovascularization. The patient underwent 23-gauge pars plana vitrectomy in the right eye. Six weeks after surgery, multimodal imaging was repeated and there was near-complete resorption of the subretinal fluid. Optical coherence tomography angiography signal superimposed on optical coherence tomography B-scan also demonstrated normal choriocapillaris signal throughout the macula. In conclusion, optical coherence tomography angiography may produce artifacts in optic disk pit maculopathy that simulate choroidal neovascularization.